Effectiveness of silhouette rendering algorithms in terrain visualisation - Che Mat, Ruzinoor; Visvalingam, Mahes (2002)
Silhouette Rendering Algorithms have been successfully used in various applications such as communicating shape and cartoon rendering.This paper explores how effective silhouette rendering algorithms could be used in terrain visualisation. This approach has been implemented in a 3D modelling system to create a new method of displaying and viewing terrain data in an artistic style. Real terrain data has been used to test the effectiveness of the algorithm.The resulting terrain images are closer to human drawn illustration than to shaded images.